Zakat and Waqf Management Training as an Effort to Build MAZAWA's Literacy Culture in East Java - Muhammad Zakki (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2023)
This study aims to educate the people of East Java about the management of the zakat and waqf sector so that it can become referenced literature regarding the benefits of effective zakat and waqf management. The study was conducted at LAZ Islamic Boarding School Mukmin Mandiri East Java in Sidoarjo. Based on this study, the author concluded several important things in this study. From the findings, the analysis that comes from the results of in-depth interviews with the Focus Group Discussion (FGD) approach, the researchers concluded as follows: 1) Zakat and Waqf training for LAZ managers in East Java, it is confirmed that training in zakat and waqf management is a basic need for zakat and waqf or LAZ managers. Where the 100 training participants agreed to say the same thing that the need for LAZ managers is training like this; 2) Zakat and Waqf training for LAZ managers in East Java, is an important thing which participants call new literacy in the field of zakat and waqf, especially in terms of managing institutions or LAZ; 3) Zakat and Waqf training for LAZ managers in East Java, not only becomes literacy or even a zakat and waqf literacy movement, but also becomes a new culture that must be internalized by zakat and waqf people in Indonesia; 4) Zakat and Waqf training for LAZ managers in East Java, is considered as a form of effort to educate human resources in Indonesia, specifically managers of zakat amil institutions or LAZ, whether those established under the auspices of Islamic boarding schools, under the auspices of Islamic mass organizations, social organizations, or those established as government agencies and private foundations that have the same goal; 5) Zakat and Waqf training for LAZ managers in East Java, generate that in order to cooperate with zakat and waqf institutions such as LAZ or BAZNAS and zakat organizations in this case FOZ (Zakat Organization Forum) so that the network is wider related to zakat and waqf. As well as being able to study management not only in finance but also in other aspects.